Journal of Experimental Zoology Part A: Ecological and Intergrative Physiology - Journal of Experimental Zoology Part A: Ecological and Intergrative Physiology (Wiley, 2026)
The Journal of Experimental Zoology – A (JEZ-A) publishes articles at the intersection of animal development, physiology, ecology, and evolution. Contributions that help to reveal how molecular, functional and ecological variation relate to one another are particularly welcome. We publish original research in the form of rapid communications or regular research articles, as well as perspectives and reviews on topics pertaining to the scope of the Journal. Acceptable articles are limited to studies on animals.
FI 1.14
Q1
Keywords: Life Sciences; Ecology & Organismal Biology; Ecología; Biología de los organismos; Acuerdos transformativos; Transformative agreements; Biología del desarrollo, fisiología, ecología y evolución en animales; Variación molecular, funcional y ecológica en zoología experimental; Estudios experimentales integrativos en mamíferos, aves y otros grupos animales